(untitled) (Research, Society and Development, 2022)
Objective: The aim of this in vitro study was to evaluate the fracture resistance of endodontically treated teeth restored with different intraradicular posts (carbon fibers, glass, or quartz) with varying post diameters (narrow, medium, or large). Methodology: One hundred and twenty bovine incisors were endodontically treated and the post space was prepared. The teeth were classified according to distinct diameters post space [Narrow (0.91-1.49mm), Medium (1.5-2.08mm), Large (2.09mm-2.67mm)] and randomly allocated to four restorative treatments: control (CO) - without post; and glass fiber (GF), carbon (CF) or quartz (QF) posts. The posts were cemented with dual-cure resin cement (Duo Link, Bisco, Schaumburg, United States) and the coronary portion was reconstructed with dual-cure resin composite (Bis-Core, Bisco, Schaumburg, United States). Fracture resistance values (N) were analyzed by two-way ANOVA and Bonferroni test (α=0.05). Results: The carbon fiber post (CF) was mechanical behavior similar to the other evaluated posts, regardless of the diameter. The control group (without post) showed the highest values of fracture resistance (1013.8 - 1127.2 N) in relation to the groups with the different evaluated posts (236.1 - 615.1 N). Within the same material, the diameter influenced the fracture strength only of the quartz fiber post, with the highest values for diameter large. Conclusion: A larger diameter only gives greater fracture resistance for QF; CF posts have similar resistance to other posts, regardless of diameter; and for large diameter, the type of post used does not differ in fracture resistance.